If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -15 = 8y + 15 Reorder the terms: -15 + -2y = 8y + 15 Reorder the terms: -15 + -2y = 15 + 8y Solving -15 + -2y = 15 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -15 + -2y + -8y = 15 + 8y + -8y Combine like terms: -2y + -8y = -10y -15 + -10y = 15 + 8y + -8y Combine like terms: 8y + -8y = 0 -15 + -10y = 15 + 0 -15 + -10y = 15 Add '15' to each side of the equation. -15 + 15 + -10y = 15 + 15 Combine like terms: -15 + 15 = 0 0 + -10y = 15 + 15 -10y = 15 + 15 Combine like terms: 15 + 15 = 30 -10y = 30 Divide each side by '-10'. y = -3 Simplifying y = -3
| 5x+4=10-5x-6 | | 2(2z-5)=3(z+5)+z | | -18+c=18+10c-13c | | -45=-2n+3 | | -20+4s-18=18-10s | | 4n=7n+2 | | 2x^2+10=8x | | 5x+2x=7x-6 | | C^2=9+16 | | -9+5x+6x=8 | | X+7-7x=-47 | | 2(10)-5y=8 | | -12+6n=15+4n+13 | | 8=-d+17 | | 7(4-3x)=2(8x-9) | | 7-14p= | | 17-6f=-5f-3 | | r+3.3=8 | | 8x-10=-8+3x | | -4=-8p+11+9p | | 6(-4x-1)=-150 | | -10-4x+8=10x-15 | | 14b+18=7+15b | | 4p+4=5p+7 | | -2-4x=6x+28 | | 3a+2b=5c | | 0.50x+13=9 | | 3x-48y=12 | | -17p-4=-16p | | 9(z-1)=16 | | 15-15x-6-45x+25-25x=0 | | 0.03(7t-9)=0.21(t-5)+0.78 |